2011
DOI: 10.1007/s00417-011-1703-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of menthol on ocular drug delivery

Abstract: Menthol may improve the ocular penetration of a drug in a transcorneal and transscleral drug delivery system without causing toxic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Many researchers have reported the use of menthol as a penetration enhancer. 39 , 40 In previous in vivo studies, we have found that the brain targeting coefficient of puerarin combined with menthol and that the brain drug targeting index were significantly higher than those obtained with injections. 34 Through studying the influence of menthol on the mucosal permeability of puerarin in the abdominal skin of Rana catesbeiana as an in vitro model, we also found that when the mass concentration of menthol was 5 mg/mL after compatibility with puerarin was assessed, the P app value was significantly higher than that obtained in the puerarin alone group.…”
Section: Discussionmentioning
confidence: 92%
“…Many researchers have reported the use of menthol as a penetration enhancer. 39 , 40 In previous in vivo studies, we have found that the brain targeting coefficient of puerarin combined with menthol and that the brain drug targeting index were significantly higher than those obtained with injections. 34 Through studying the influence of menthol on the mucosal permeability of puerarin in the abdominal skin of Rana catesbeiana as an in vitro model, we also found that when the mass concentration of menthol was 5 mg/mL after compatibility with puerarin was assessed, the P app value was significantly higher than that obtained in the puerarin alone group.…”
Section: Discussionmentioning
confidence: 92%
“…Menthol is a naturally‐occurring cyclic terpene alcohol of plant origin, which frequently used in the preparation of topical analgesic, antipruritic and anti‐inflammatory drug, and as a penetration enhancer of drugs . Menthol is also as messenger drug performs a good penetration enhancer, such as enhancing permeation of drugs of skin, improving the drug delivery into the eye tissues and enhancing the gene transfer efficiency . The mechanism of menthol as a penetration enhancer is affecting intracellular lipids or proteins and loosens the epithelium junctions when present in high concentrations in the epithelium .…”
Section: Discussionmentioning
confidence: 99%
“…Menthol is also as messenger drug performs a good penetration enhancer, such as enhancing permeation of drugs of skin, improving the drug delivery into the eye tissues and enhancing the gene transfer efficiency . The mechanism of menthol as a penetration enhancer is affecting intracellular lipids or proteins and loosens the epithelium junctions when present in high concentrations in the epithelium . Combination therapies of TCM provided combined action on the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, L-menthol is preferably included as an algefacient in over-the-counter eye drops [1]. Because L-menthol is a hydrophobic compound, it has a tendency to be adsorbed onto the walls of eye-drop containers, which are commonly made of polyolefin resin.…”
Section: Introductionmentioning
confidence: 99%